Senior Managers’ Sensemaking and Responses to Strategic Change - Balogun, Julia; Bartunek, Jean M.; Do, Boram (Organization Science, 2015)
Our longitudinal study of the sensemaking and responses to strategic change of the senior management team of a UK multinational subsidiary provides unusual data that enable us to explore the complexity of senior team change related sensemaking. We show senior teams to be distinct interpretive communities rather than one homogeneous category of change agents, as typically portrayed in change literature, who at times of center-led strategic change occupy a complex dual recipient/change agent role. By adopting a narrative approach, we show the shared sensemaking of such a team to be impacted by the locally differentiated nature of its interpretive and relational contexts, leading to context specific interpretations of center-led change and locally distinct responses, with consequences for change outcomes. We found that because of their dual role, senior managers construct two sets of interwoven and interacting change narratives which mediate the relationship between the wider organizational change and local change actions. Our analysis reveals how these evaluations of change, accompanied by affect, evolve over time and how they impact action. These findings contribute to existing theories of sensemaking and change by addressing the previously undertheorized relationship between senior management teams’ sensemaking and their responses to strategic change.